KETIDAKNYAMANAN PASCA PERSALINAN: ANALISIS KONSEPTUAL DAMPAK DIASTASIS RECTUS ABDOMINIS (DRA) TERHADAP IBU POSTPARTUM - Hemi Fitriani; Setyowati Setyowati; Yati Afiyanti; Yeni Rustina (Media Penelitian dan Pengembangan Kesehatan, 2025)
Diastasis rectus abdominis (DRA) in postpartum mothers has a high prevalence, with 85% experiencing this condition, leading to various complaints. However, clinical management remains limited due to the lack of consensus on symptom boundaries and clinical impacts. This study aims to analyze the concept of discomfort due to DRA in postpartum mothers using Walker and Avant’s approach. A descriptive method with concept analysis was applied. Literature search using international electronic databases with a global scope including Scopus, ScienceDirect, MEDLINE, EBSCO, ProQuest, and SAGE, using keywords such as "diastasis rectus abdominis," "interrectus abdominis," "postpartum," and "impact." Inclusion criteria were open-access, including literature review, and full-text articles published from 2018 to 2024. Articles that did not address antecedents, attributes, or consequences of discomfort were excluded. A total of 28 out of 88 identified articles were analyzed, covering various fields such as obstetrics, gynecology, surgery, physiotherapy, radiology, nursing, and public health. The study concludes that discomfort due to DRA consists of primary and secondary symptoms. Primary symptoms include a distended abdomen, abdominal pain, kinesiophobia, impaired self-concept, disturbed social interaction, and reduced quality of life. Secondary discomfort includes hunched posture, back and pelvic pain, spinal and pelvic instability, pelvic floor disorders, and gastrointestinal issues. This categorization of discomfort is expected to establish clearer symptom boundaries. Defining these symptoms can help develop standardized clinical practice guidelines, ensuring more effective diagnosis and treatment for postpartum mothers with DRA.